Administrative Management Training for Development of Information Technology-Based Apparatus and Community Soft Skills in Pelabuhan Dalam Village - Ali Ibrahim; Yadi Utama; Ermatita; Putri Eka Sevtiyuni (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2022)
Administrative Management Training Activities for the Development of Information Technology-Based Officials and Society Softskills in Pelabuhan Dalam Village are carried out in accordance with the results of discussions between the PKM team and the village head. In selecting topics, training activities are adjusted to the needs of village officials and communities. This is based on the importance of IT for society in facing the demands of the times and the development of the IT world. The training activities started with the preparation of the PKM team in the multimedia laboratory and game programming at the Faculty of Computer Science, Sriwijaya University. Then continued with the PKM team's survey to the location and further discussions with the village head and village officials for the implementation of PKM activities. The result of this activity is the knowledge of the village community with IT, to deal with the development of the IT world.